Implementation of Wadi'ah Academic In Sharia Banking - Choiriyah Choiriyah; Dwi Noviani; Richway Richway (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2023)
Public interest in muamalah according to shari'ah is a growing factor in the Indonesian economy. To develop society, the principle of Islamic Banking Institutions or Syari'ah Banking is to dismantle the interest system and replace it with a system for measuring the results of savings and loan operations. The most common form of fundraising contract in Islamic banks is the savings contract, which is also known as the wadi'ah contract. This study uses a constructive paradigm with a qualitative descriptive analysis for this type of research conducted on the literature. To process data, users use two types: secondary data and primary data. Data collection techniques are carried out using documentation studies. Data analysis uses content analysis with a more thorough process which includes categorization and selection in an in-depth format. In the process of collecting and analyzing data, researchers used two models of triangulation of sources. According to evidence, Wadi'ah helps those in need. Based on its application in Islamic banking, the term